1994
DOI: 10.1210/endo.134.2.8299560
|View full text |Cite
|
Sign up to set email alerts
|

17 beta-estradiol and parathyroid hormone potentiate each other's stimulatory effects on alkaline phosphatase activity in SaOS-2 cells in a differentiation-dependent manner.

Abstract: We studied the effects of 17 beta-estradiol (E2) and PTH on alkaline phosphatase activity in SaOS-2 cells that had been passaged and grown continually in the presence (SaOS + Dex) or absence (SaOS - Dex) of 10(-8) M dexamethasone (Dex). We showed that the more differentiated SaOS + Dex cells had higher alkaline phosphatase activity and PTH-responsive adenylate cyclase than the less differentiated SaOS - Dex cells. In SaOS - Dex cells, E2 or PTH (1 x 10(-11)-1 x 10(-6) M) had no effect on alkaline phosphatase a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
20
1

Year Published

1995
1995
2003
2003

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 9 publications
8
20
1
Order By: Relevance
“…The stimulatory effect of intermittently added E 2 on mineralized bone nodule formation in these more differentiated cells provide stronger evidence for our previous hypothesis [21][22][23][24] that the effect of E 2 is differentiation-stage dependent. The mechanisms involved in the differential response of the cells to continuous vs. intermittent treatment with E 2 are not clear at the present time.…”
Section: )supporting
confidence: 69%
See 4 more Smart Citations
“…The stimulatory effect of intermittently added E 2 on mineralized bone nodule formation in these more differentiated cells provide stronger evidence for our previous hypothesis [21][22][23][24] that the effect of E 2 is differentiation-stage dependent. The mechanisms involved in the differential response of the cells to continuous vs. intermittent treatment with E 2 are not clear at the present time.…”
Section: )supporting
confidence: 69%
“…[21][22][23][24] We later demonstrated that the more differentiated SaOSϩDex cells had greater immunohistochemically detectable ERa. 21) In this study we have further established and characterized a third and more differentiated model of cells that mineralizes in culture, by culturing SaOSϩ Dex cells in the presence of ascorbic acid and b-glycerophosphate.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations